Coupling fractionation and batch desorption to understand arsenic and fluoride co-contamination in the aquifer system. (December 2016) - Kumar, Manish; Das, Nilotpal; Goswami, Ritusmita; Sarma, Kali Prasad; Bhattacharya, Prosun; Ramanathan, AL.
Abstract: The present work is an attempt to study As and F+ coevality using laboratory based assays which couples fractionation and batch dissolution experiments. Sequential extraction procedure (SEP) resulting into five "operationally defined phases", was performed on sediment and soil samples collected from the Brahmaputra flood plains, Assam, India. High correlation between the Fe (hydr)oxide fraction and total As content of the soil/sediment sample indicates the involvement of Fe (hydr)oxides as the principal source of As. F − being an anion has high potential to be sorbed onto positively charged surfaces. Findings of the SEP were used to design the batch desorption experiments by controlling the Fe (hydr)oxide content of the soil/sediment. Desorption of As and F − was observed under acidic, neutral and alkaline pH from untreated and Fe (hydr)oxide removed samples. Highest amount of As and F − were found to be released from untreated samples under alkaline pH, while the amount leached from samples with no Fe (hydr)oxide was low. The study showed that the Fe (hydr)oxide fraction commonly found in the soils and sediments, had high affinity for negatively charged species like F − oxyanions of As, AsO4 3− (arsenate) and AsO3 3− (arsenite). Fe (hydr)oxide fraction was found to play the major role in co-evolution of As and F − . Two sorption coefficients were proposed based on easily leachable fraction and As present in the groundwater of sampling location for understanding of contamination vulnerability from the leaching. Graphical abstract: Highlights: Organic matter, clay and Fe (hydr)oxide content governs partition coefficient of As. Outer and inner surface complexed As were easily leachable but small As reserves. Fe (hydr)oxide bound arsenic was the most prominent single redox dependent fraction. Fe (hydr)oxide fraction play the major role in co-evolution of As and F − .